2021
DOI: 10.1097/mpg.0000000000003147
|View full text |Cite
|
Sign up to set email alerts
|

Supplementary Bovine Colostrum Feedings to Formula‐Fed Preterm Pigs Improve Gut Function and Reduce Necrotizing Enterocolitis

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Thus, initial TPN administration followed by initiation of enteral feeds has been used in several established models of NEC in swine ( 16 , 18 , 24 , 25 , 31 , 59 , 60 ). Often, these studies continue the administration of TPN at lower rates while simultaneously administering enteral feeds for 18–120 h ( 18 , 29 31 , 37 , 59 63 ). On the other hand, other investigators have developed piglet NEC models using enteral feeds exclusively for NEC induction ( 64 66 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, initial TPN administration followed by initiation of enteral feeds has been used in several established models of NEC in swine ( 16 , 18 , 24 , 25 , 31 , 59 , 60 ). Often, these studies continue the administration of TPN at lower rates while simultaneously administering enteral feeds for 18–120 h ( 18 , 29 31 , 37 , 59 63 ). On the other hand, other investigators have developed piglet NEC models using enteral feeds exclusively for NEC induction ( 64 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…After euthanasia, a midline laparotomy was performed, and the intestine examined in situ . A gross injury score was assigned to the small intestine (proximal, mid, and distal segments) and colon based on the most severely affected area assessed independently by two graders using an adaptation of a published scoring system ( 16 , 37 ). Scores ranged from 1 (no injury) to 6 (most severe injury) using the criteria shown in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…blood neutrophils, Treg cells, gut IL8 response). Further, Pan et al demonstrated epigenetic programming and NEC-protective effects of early colostrum supplementation on gut mucosal immunity and gene expression in newborn preterm pigs on parenteral nutrition (44,49). In either case, the effects may be mediated by local species-unspecific immunoglobulin binding of pathogens and modulation of local mucosal immune responses (50,51).…”
Section: Diet and Postnatal Immune Developmentmentioning
confidence: 99%
“…Indeed, these compounds have together the potential to promote antimicrobial and immunoregulatory activities, as well as growth performance. Bovine colostrum contains bioactive molecules with immunoregulatory and antimicrobial properties that are essential for the development of the immune system (Cross and Gill, 2000;Schlimme et al, 2000;Sugiharto et al, 2015;Lo Verso et al, 2020a;Yan et al, 2021) and modulating the inflammatory response to pathogens (Blais et al, 2015). The interest surrounding the supplementation of yeast extract is driven by its content in active components such as enzyme, nucleic acids, and cell wall products such as β-glucan and mannans.…”
Section: Introductionmentioning
confidence: 99%